Dialectal and sociolinguistic patterns of postnuclear / s/ variation in Spanish - Vida Castro, Matilde; Villena Ponsoda, Juan Andrés; Molina Martos, Isabel (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper presents a panoramic vision over the lenition process of postnuclear /‑s/ in Spanish. First, the universal linguistic trends that operate over the variable realization of this particular feature in the different Spanish speech communites and produce similar outcomes in other languages are presented. After that, the main postnuclear /-s/ variable continua in European and American Spanish are described and the results of different sociolinguistic studies about several Spanish speech communities are compared. Finally, the first results of a joint analysis conducted in the frame of the Preseea project of two Spanish varieties contrasted by the realization of this feature are presented: Vallecas, a conservative variety that presents relatively high indexes of aspiration promoted by specific social groups and Malaga, an innovative variety where aspiration is mainly determined by internal factors.